Analysis of Economic Growth and Base Sectors in West Sulawesi Province 2015-2021 - Awal Nopriyanto Bahasaoan; Aswar Rahmat; Taufik Hidayat BTahawa; Farida Millias Tuty; Meldilianus Nabas J. Lenas (Jurnal Mantik, 2022)
The economic structure of West Sulawesi Province according to business fields is still dominated by the agricultural, forestry and fisheries sectors. Since 2016-2020, it has contributed more than 40% of the total GRDP. The economy of West Sulawesi Province in terms of average economic growth in 2015-2019, Mamuju Regency has the highest growth among other Regencies. This is influenced by the existence of Mamuju Regency as the capital of West Sulawesi Province. So that Mamuju Regency becomes the center of government and the center of economic activity. Mamuju Regency has an average growth rate of 7 percent (BPS, 2011). The purpose of this study is to find out the pattern and structure of economic growth and the sector base of West Sulawesi Province 2015-2020. The analytical method used in this study is the Klassen Typology and the Location Question (LQ). Based on the Klassen Typology analysis, the area of ??West Sulawesi Province can be mapped into 4 types. The area that is in the fast-developing and fast-growing category is only Mamuju Regency. An advanced but depressed area is the Pasangkayu Regency. The fast developing region is Polewali Mandar Regency and the underdeveloped areas in West Sulawesi Province have 3 regencies, namely Majene, Mamasa and Central Mamuju. Based on the Location Question (LQ) analysis, each district in West Sulawesi Province has an advantage or base sector which is a regional potential that can increase regional economic growth. Mamuju Regency has 13 base sectors, Polewali Mandar Regency has 10 base sectors,